RELATIONSHIP KNOWLEDGE LEVEL OF NURSES ABOUT STANDARDS OF NURSING CARE WITH APPLICATION NURSING CARE DOCUMENTATION - Agung Dwi Ardianto; Fitriana Kurniasari Solikhah (STIKes Kepanjen, 2021)
Nursing documentation must be carried out at each stage of nursing care, so that it can be a means of nurse communication at work. Nursing documentation is a manifestation of nurses' accountability if nursing care services are disputed in the legal sphere. The phenomena, there are still many nurses who have not implemented nursing care documentation properly and correctly. The study was a correlational design with a population of all nurses in the inpatient unit of Bantur Public Centre Health, with a purposive sampling technique and a large sample of 14 people. Data collection using questionnaire instruments. The results showed that the majority of respondents (50%) applied sufficient nursing care documentation, the majority of respondents (58%) had sufficient knowledge. From the results of the Spearman statistical test, it is known, rho count = 0.923 and p value = 0, there is a correlation between the level of nurse knowledge about the standard of nursing care and the application of nursing care documentation. implementing of nursing documentation properly and correctly, it is necessary to have good knowledge about Nursing Care Standards. The better the knowledge about the standard of nursing care, the better the nursing care documentation that is applied